TETANUS: A CLINICAL CASE REVIEW IN COTOPAXI ECUADOR - García Heredia, Gloria (2018)
Tetanus is an acute, serious and life-threatening infectious disease that affects the nervous system. It is caused by a neurotoxin called tetanospasmin produced by the bacterium clostridium  tetani. This infection is infrequent and is not contagious; but it still occasionally affects our population. The clinical case of a 65-year-old patient, who was admitted to the IESS General Hospital of Latacunga, province of Cotopaxi, due to a post-traumatic injury in the left leg and ten days later, she developed generalized  tetanus, is presented. The patient was unaware of her history of childhood  immuni zations and never received tetanus vaccine as an adult. Initially the patient exhibited with dysphagia and trismus and 24 hours later it evolved with an increase in generalized muscle tone and respiratory muscle compromise, so she was admitted to the intensive care unit  where she remained for six weeks. She was given antitetanus immunoglobulin, tetanus antitoxin, antibiotic therapy, muscle relaxants and supportive treatment. The superinfected wound required skin graft after which it achie ved full recovery. Regarding this case, a brief update of the literature about this unusual pathology was made, due to the systematic immunization included in the national immunization strategy, which has a fatality rate around 30%.